Evaluating the Effect of Jammer Radiation on Learning and Memory in Male Rats - Mehrnaz Yazdanpanahi; Abasaleh Namazi; Manzar Banoo Shojaeifard; Samaneh Nematollahii; Saeedeh Pourahmad (Journal of Biomedical Physics and Engineering, 2023)
Background: Previous studies shown that mobile phone can impairment of working memory in humans. Objective: In this study, the effect of radiofrequency radiation emitted from common mobile jammers have been studied on the learning and memory of rats.Material and Methods: In this prospective study, 90 Sprague-Dawley rats, were divided into 9 groups (N=10): Control, Sham1st (exposed to a switched-off mobile jammer device at a distance of 50 or 100 cm/1 day, 2 hours), Sham2nd (similar to Sham1st, but for 14 days, 2 h/day), Experimental1st -50 cm/1 day &100 cm/1 day (exposed to a switched-on device at a distance of 50 or 100 cm for 2 hours), Experimental2nd (similar to experimental1st, but for 14 days, 2 h/day). The animals were tested for learning and memory the next day, by the shuttle box. The time that a rat took to enter the dark part was considered as memory. Results: Mean short-term memory was shorter in the experimental- 50 cm/1 day than control and sham- 50 cm/1 day (P=0.034), long-term memory was similar. Mean short- and long-term memory were similar in the experimental- 100 cm/1 day, control and sham- 100 cm/1 day (P>0.05). Mean short-term memory was similar in experimental- 50 cm/14 days, control, and sham- 50 cm/14 days (P=0.087), but long-term learning memory was shorter in the radiated group (P=0.038). Mean short- and long-term were similar among experimental-100 cm/14 days, control or sham 100 cm/14 days (P>0.05).  Conclusion: Rats exposed to jammer device showed dysfunction in short- and long-term memory, which shown the unfavorable effect of jammer on memory and learning. Our results indicated that the distance from radiation source was more important than the duration.